Willingness to communicate and second language speech fluency: An idiodynamic investigation. (August 2016) - Wood, David
Abstract: Second language (L2) speech fluency has usually been studied as a function of a set of measurable temporal features of speech, but it has seldom been researched in relation to learner or situational factors in performance such as willingness to communicate (WTC), definable as readiness to engage in communication at a specific time and with specific interlocutors. The present study is an examination of the fluid relationship between WTC and L2 fluency from a dynamic systems perspective. The exploratory case study presents an examination of WTC and fluency in Japanese learners of English L2, in communication with a non-Japanese interlocutor. Speech samples produced by the learners were analyzed for markers of fluency. The learners produced WTC profiles for their speech samples by creating bitmaps during stimulated recall, and also provided retrospective self-analysis of WTC in stimulated recall. The fluency profiles and WTC profiles were matched and analyzed to explore the interrelationship between fluency and WTC. The results illuminate the relationship between fluency and WTC, particularly the fluidity and possible directionality of the relationship, i.e. whether fluency breakdowns lead to lowered WTC or vice versa.